(untitled) (The Conference Hub, 2025)
This article examines the pedagogical views of Abdulla Avlani, an eminent figure in the field of education, who is known for his innovative and student-oriented approach to education. Avlani’s philosophy emphasizes personalized learning, critical thinking, creativity, and fostering a supportive learning environment. In this study, the main principles of Avloni’s pedagogical views and their impact on modern educational practice are studied.